Effect of Cu-N co-doping on the dielectric properties of ZnO nanoparticles. (10th November 2022) - Kaur, Manpreet; Kumar, Vishesh; Singh, Jagbir; Datt, Jagmohan; Sharma, Rakesh
ABSTRACT: In the current study, Zn1-x Cux O0.997 N0.003 nanoparticles (x = 0–0.04) were synthesised using the co-precipitation technique. The formation of the hexagonal wurtzite phase of ZnO in all samples was confirmed by XRD.  The existence of defects and structural disorders in co-doped ZnO nanoparticles were confirmed by the Rietveld Refinement and Raman analysis. The SEM and TEM images inferred the transformation of nanoparticles from the hexagonal to ellipsoidal shape. EDX analysis confirmed that the atom weight % of all samples was found to be similar to previously reported values. FTIR spectroscopyand XPS inferred the substitution of Cu + and N −3 ions at vacancies in ZnO. UV-vis spectra showed decrease in the band gap with increase in the dopant concentration. The dielectric constant and ac conductivity were found to be maximum at highest Cu doping due to the small band gap, small crystallite size and overlap of Cu 3 d and N 2 p orbitals.